Testing The Impact Of The Central Bank's Support For The Experience Of Converting The Conventional Banks Into Islamic In Libya Multiple-groups Analysis Using Structural Equation Modeling - Muhammad Ridhwan Ab. Aziz; Fuadah Johari; Marai .A .D Abdalla (International Journal Of Science And Research, 2024)
Volume 4 Issue 9, September 2015